Update On Performance And Return To Sport After Biceps Tenodesis In Professional Baseball Players (226). Issue 10 (31st October 2021) - Erickson, Brandon; Chalmers, Peter; Dangelo, John; Ma, Kevin; Rowe, Dana; Ciccotti, Michael; Romeo, Anthony
Objectives: Determine the return to sport (RTS) rate and performance upon RTS in professional baseball players who underwent biceps tenodesis. Methods: All professional baseball pitchers who underwent biceps tenodesis between 2014 and 2017 were included. Players with concomitant rotator cuff repair were excluded. Demographic and performance data (preoperative and postoperative) were recorded for each player. Performance metrics were then compared between the biceps tenodesis and matched control (no history of biceps tenodeses) groups. Results: 14 players (average age 27±4 years; 12 pitchers, 2 position outfielders) were included. Most (79%) were open subpectoral tenodeses while one was an arthroscopic biceps transfer and one was arthroscopic suprapectoral. Fixation methods included cortical button (42%), interference screw (25%), suture anchor (25%) and drill holes (8%). Most players (79%) underwent concomitant procedures (43% underwent SLAP repair). Among the 14 players, 2 were unable to RTS, 5 RTS but to a lower level, and 7 RTS at the same or a higher level. Thus, overall, while 86% (12/14) were able to RTS, 50% (7/14) were able to return to the same or a better level and 50% were either unable to return or returned to a lower level. Among pitchers specifically, 100% (12/12) were able to return to play, but only 50% (6/12) were able to return to the same or a higher level. For those players who did return to play, it took 245±84 days, their performance was unchanged and did not differ from matched controls. Conclusions: While 86% of professional baseball players returned to sport following biceps tenodesis, only 50% returned at the same or higher level. No decline in performance was noted in players who successfully returned. Open subpectoral tenodesis is the most common tenodesis technique performed on professional baseball players.